A New Routing Approach for Mobile Ad Hoc Systems Based on Fuzzy Petri Nets and Ant System - Kacem, Ibrahim; Sait, Belkacem; Mekhilef, Saad; Sabeur, Nassereddine (Institute of Electrical and Electronics Engineers, 2018)
Mobile ad hoc network (commonly called MANET) comprises a large and relatively dense population of mobile units that move in any territory, and its only means of communication is the use of wireless interfaces without using pre-existing infrastructure or centralized administration. Moreover, routing should provide a strategy for sending data at any time between a pair of nodes (i.e., source and destination) across a network. However, the main problem is to determine an optimal routing of packets across the network. The main objective of the proposed protocol is to find the least-cost investment in nominal capacities that ensures the routing of nominal traffic and guarantees its survivability in case of any arc or node failure. In this context, the fuzzy synchronized Petri net is substantially adopted in the modeling of the routing and detection/decision functions that use a synchronized fuzzy transition approach, where the ant system is used to find a solution for the problem of uncertainty events in ad hoc networks. The obtained results show the effectiveness of the proposed synchronized Fuzzy Ant System (SynFAnt) protocol compared to four protocols. The SynFAnt routing protocol improves the packet delivery ratio, the throughput, the end-to-end delay, and the acceptance rate of the QoS flows.